Product Modularity, Mass customization Supply Chain Quality Integration and The Competitive Performance of Textile and Appraisal Sector of Indonesia: The Role of Open Book Accounting - Natnaporn Aeknarajindawat; Suramon Chancharoen (International Journal of Supply Chain Management, 2019)
The main purpose of the current study is to investigate the impact of product modularity, Mass customization, and supply chain integration on the competitive performance of the textile and appraisal sector of Indonesia. In addition to that the study has also examined the moderating role of open book accounting in the relationship between product modularity and competitive performance and in the relationship between supply chain quality integration and competitive performance. The hypotheses have been developed using the existing theories and the objectives have been set for the study. The data was collected using survey method. Quantitative research approach was used to gather information from a sizeable population. A resourceful finding related to product modularity, supply chain quality management, and mass customization has been added to the existing literature. The previous empirical studies focused on the development of mass customization capability and no study has paid any attention on the role of open book accounting in the supply chain management. The research offers several guidelines for the managers to implement supply chain integration. It has been suggested that the managers should apply organizational and manufacturing design practices, which enhance the capability of mass customization for managing internal and external issues related to supply chain.